2021
DOI: 10.1177/08927057211021462
|View full text |Cite
|
Sign up to set email alerts
|

Linear translaminar fracture characterization of additive manufactured continuous carbon fiber reinforced thermoplastic

Abstract: This work presents the experimental determination of fracture mechanics parameters of composite specimens manufactured by fused filament fabrication (FFF) with continuous carbon fiber reinforced thermoplastic filaments, based on Linear Elastic Fracture Mechanics (LEFM). The critical mode I translaminar fracture toughness (KIc) and the critical energy release rate (GIc) are found for unidirectional and cross-ply laminates. The specimens were submitted to quasi-static tensile testing. Digital Image Correlation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
(96 reference statements)
0
11
0
Order By: Relevance
“…For 3D-printed CFRCs, research in terms of translaminar fracture toughness focused on the mode I translaminar fracture toughness. According to the ASTM D5045 Translaminar ASTM D5045 [47,48] ASTM E1922-04 [49] ASTM STP 410 [50] Mode II Interlaminar ASTM D7905 [24,37,40,51] ISO 15114 [39,40,42] Mixed mode Interlaminar ASTM D6671 [40] standard, the compact tension (CT) was used to characterize mode I fracture toughness. 47 In addition, testing of semi-circular Bending (SCB) specimens and double edge notch tension (DET) specimens could also be applied to characterize mode I fracture toughness in 3D-printed continuous fiber reinforced specimens.…”
Section: Fracture Toughness Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For 3D-printed CFRCs, research in terms of translaminar fracture toughness focused on the mode I translaminar fracture toughness. According to the ASTM D5045 Translaminar ASTM D5045 [47,48] ASTM E1922-04 [49] ASTM STP 410 [50] Mode II Interlaminar ASTM D7905 [24,37,40,51] ISO 15114 [39,40,42] Mixed mode Interlaminar ASTM D6671 [40] standard, the compact tension (CT) was used to characterize mode I fracture toughness. 47 In addition, testing of semi-circular Bending (SCB) specimens and double edge notch tension (DET) specimens could also be applied to characterize mode I fracture toughness in 3D-printed continuous fiber reinforced specimens.…”
Section: Fracture Toughness Test Methodsmentioning
confidence: 99%
“…47 In addition, testing of semi-circular Bending (SCB) specimens and double edge notch tension (DET) specimens could also be applied to characterize mode I fracture toughness in 3D-printed continuous fiber reinforced specimens. 50,54 Besides, according to ASTM E1922-04, Zhang et al 49 conducted the uniaxial tensile tests of single-edge notched plates to characterize the translaminar fracture toughness of 3D-printed CFRCs. Lastly, to the authors' knowledge, there were few studies about the intralaminar fracture toughness of 3D-printed CFRCs due to the lack of accepted standards.…”
Section: Fracture Toughness Test Methodsmentioning
confidence: 99%
“…The result indicated that composite parts can be used to support load during tension, as the ruptured fibers in the fracture interface showed that the load was effectively transferred from the matrix to the fiber reinforcement for better properties. 61 Figure 12(c) and (d) show the optical micrographs of specimens with grid and triangular infill patterns after performing flexural test. A ruptured region can be observed, where the maximum bending force was applied, and the layers were fractured.…”
Section: Fracture Interface Study Of the 3d Printed Porous Ccfrpc Str...mentioning
confidence: 99%
“…The result indicated that composite parts can be used to support load during tension, as the ruptured fibers in the fracture interface showed that the load was effectively transferred from the matrix to the fiber reinforcement for better properties. 61
Figure 12.The optical micrographs of the 3D printed porous composite specimen’s fracture interface after performing; tensile test with (a) grid infill pattern (b) triangular infill pattern; and flexural test with (c) grid infill pattern (d) triangular infill pattern.
…”
Section: Materials Experimental Set-up and Testing Proceduresmentioning
confidence: 99%
“…Over recent years, the Additive Manufacturing (AM) of reinforced polymers has been playing an important role in the production of high-performance components, opening the door for new applications in the manufacturing of lightweight structures. Inserted into the material extrusion-based category, the Fused Filament Fabrication (FFF) [ 1 , 2 , 3 , 4 , 5 , 6 ], often referred to by the term 3D printing, is an Additive Manufacturing process that can work with continuous fiber-reinforced thermoplastics [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. From a mechanical behavior point of view, both the printing process parameters and individual constituent characteristics, e.g., fiber distribution, affect the resulting performance of 3D-printed composite materials [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%